A framework for laboratory pre-work based on the concepts, tools and techniques questioning method - J. Huntula (2018)
Learning in the laboratory is different from learning in other contexts because students have to engage with various aspects of the practice of science. They have to use many skills and knowledge in parallel - not only to understand the concepts of physics but also to use the tools and analyse the data. The question arises, how to best guide students' learning in the laboratory. This study is about creating and using questions with a specifically designed framework to aid learning in the laboratory. The concepts, tools and techniques questioning (CTTQ) method was initially designed and used at Mahidol University, Thailand, and was subsequently extended to laboratory pre-work at the University of Sydney. The CTTQ method was implemented in Sydney with 190 first-year students. Three pre-work exercises on a series of electrical experiments were created based on the CTTQ method. The pre-works were completed individually and submitted before the experiment started. Analysed pre-work, surveys and interviews were used to evaluate the pre-work questions in this study. The results indicated that the CTTQ method was successful and the flow in the experiments was better than that in the previous year. At the same time students had difficulty with the last experiment in the sequence and with techniques. © 2011 IOP Publishing Ltd.